2014
DOI: 10.1177/0095244314557973
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of poly(lactic acid)/hydroxyapatite prepared by a solvent-blending technique

Abstract: Poly(lactic acid) (PLA) was solvent blended in a chloroform solution using multiple weight fractions of hydroxyapatite (HAp) (5, 10, and 20 wt%). A miniature laboratory mixing extruder equipped with a ribbon die was used to produce thin ribbons of PLA/HAp biocomposites. The dynamic mechanical parameters (storage modulus (G′), loss modulus (G′′), complex viscosity (η*), and degree of crystallinity) increased with increasing HAp loading. In vitro hydrolytic degradation of the PLA biocomposites was conducted in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 35 publications
2
4
1
Order By: Relevance
“…As shown in Figure 1 This phenomenon was also found when PLA was added by hydroxyapatite with more quantity (0-20% wt), as reported in our previous work (Kaavessina et al 2015). Tg can be concluded in constant value due to only shifting about 1-2 °C.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…As shown in Figure 1 This phenomenon was also found when PLA was added by hydroxyapatite with more quantity (0-20% wt), as reported in our previous work (Kaavessina et al 2015). Tg can be concluded in constant value due to only shifting about 1-2 °C.…”
Section: Resultssupporting
confidence: 82%
“…Again, this increase in crystallinity might be due to filler acting as a nucleating agent. A similar result was reported in our previous work on PLA/hydroxyapatite composite (Kaavessina et al 2015).…”
Section: )supporting
confidence: 92%
“…The weight loss of the fibers was below 5% during the period studied. Some authors have reported a weight loss of 27% after 16 weeks [4], 3% after 5 weeks [99], and 37% after 28 days (almost 4 weeks) [100] for in vitro hydrolytic degradation of PLA.…”
Section: Fiber Hydrolytic Degradationmentioning
confidence: 99%
“…This process involves the scission of PLA chains that are dominant in ester bonds concentrated in this phase to generate a lower M W PLA or monomer (lactic acid). Thus, the degradation occurs preferentially in the amorphous phase and then continues to the crystalline phase [ 29 , 30 , 31 ]. The rough surface and numerous micro-holes could be ascribed to PLA chain scission and removal in both phases.…”
Section: Resultsmentioning
confidence: 99%